COVID-19 Fears and Preventive Behaviors among Prison Staff - da Cunha Gonçalves, Leonel (Victims & offenders, 2023)
This study focused on COVID-19 preventive behaviors and fears among prison staff members after the first wave of the pandemic. Cross-sectional data from 171 participants were collected in Switzerland. The level of fears (58.5%) and protective behaviors (100%) were high. Correctional officers adhered less to preventive measures than other staff members (p = .001). Fears were related to a reduction of social contacts (p = .006) and worries about physical health was related to preventive behaviors in general (p = .006). There is a need to raise prison staff awareness regarding their vulnerability to the SARS-CoV-2 in order to improve the effectiveness of health campaigns in prison settings. Special attention should be given to correctional officers.